Significance of Hesed in the Blessing of Naomi: Exegetical and Theological Study of Ruth 1:8, 9 - Abin, Blasius (Klabat Theological Review, 2021)
The connection of hesed and covenant commitment is a pivotal point in the covenant between Ruth and Naomi. The blessing of Naomi indicates that there are two agents of hesed, namely God’s hesed for the two Moabite women in the future, and the hesed of the two Moabite women for Naomi’s family in the past. Naomi uses the term hesed in Ruth 1:8b without giving a specific description of God’s hesed. However, the oracle in Ruth 1: 9a Naomi specifies the idea of God’s hesed. Through the exegetical and theological study of the text, the words of Naomi imply that the past continual covenant faithfulness of two Moabite women to Elimelech’s family as well as to God is the basis of Naomi’s supplication that God should reward them hesed in the future. The theological implication is that the faithfulness of human beings to the covenant commitment assures the permanence of hesed in the covenant relationship. Moreover, faithfulness to covenant commitment stood out as being a means of how God worked out His redemptive plan to turn about the human crisis. To sum, hesed is considered as the content of the covenant, and it is the basis on which the covenant relationship will be enabled to continue. Keywords: Hesed; Covenant; Commitment References Arnold, Bill T., and John H. Choi. A Guide to Biblical Hebrew Syntax. Cambridge, UK: Cambridge University Press, 2007. Baer, David A., and Robert P. Gordon. “חֶסֶד.” New International Dictionary of Old Testament Theology and Exegesis. Ed. W. A. VanGemeren. Grand Rapids, MI: Zondervan, 1997. Badillos, Angel Saenz. A History of the Hebrew Language. Trans. John Elwolde. Cambridge, MA: Harvard University Press, 1993. Bible Works, Biblical Database Software for Microsoft Windows, version 7.o.o12x. Bible Works, LLC. Hermeneutika Computer Bible Research Software. חֶסֶד, MT, 2007. Brown, Francis, with S. R. Driver and Charles A. Briggs. A Hebrew and English Lexicon of the Old Testament With an Appendix Containing the Biblical Aramaic. Based on the lexicon of William Gesenius. Oxford: Clarendon, 1952, s.v. “חֶסֶד.” Bruce K., M. O’Connor. An Introduction to Biblical Hebrew Syntax. Winona Lake, IN: Eisenbrauns, 1990. Bush, Frederic W. Ruth/Esther. Word Biblical Commentary 9. Dallas, TX: Word, 1996. Buttrick, George Arthur. “Ruth.” The Interpreter’s Bible. Nashville, TN: Abingdon, 1953. Campbell, Edward F. Jr. Ruth: A New Translation with Introduction and Commentary. Anchor Bible. Garden City, NY: Doubleday, 1975. ________________. “The Hebrew Short Story: A Study of Ruth.” A Light Unto My Path. Ed. H. Bream, R. Heim, and C. Moore. Philadelphia: Temple University Press, 1974. Clark, Gordon R. The Word Heseḏ in the Hebrew Bible. Journal for the Study of the Old Testament Supplement Series 157. Sheffield, UK: Academic, 1993. Clines, David J. A. The Dictionary of Classical Hebrew. Sheffield, UK: Academic, 1998. s.v. “חֶסֶד.” Cogan, Mordechai, and Hayim Tadmor. II Kings: A New Translation With Introduction and Commentary. New York, NY: Doubleday, 1988. Cohen, Ada Taggar. “Political Loyalty in the Biblical Account of 1 Samuel xx-xxii in the Light of Hittite Texts.” Vetus Testamentum 55 (2005): 251-268. Collins, C. John. Genesis 1-4: Linguistic, Literary, and Theological Commentary. New Jersey, NJ: P & R, 2006. Daniel I. Judges, Ruth. The New American Commentary 6. Nashville, TN: Broadman & Holman, 1999. Exum, J. Cheryl. Plotted, Shot, and Painted: Cultural Representations of Biblical Women. JSOTSup 215. Sheffield, UK: Academic, 1996. Fensham, Charles. ”The Treaty Between Israel and the Gibeonites.” Biblical Archaeologist 27 (1964): 96-100. Hamilton, Victor P. Handbook on the Historical Books: Joshua, Judges, Ruth, Samuel, Kings, Chronicles, Ezra-Nehemiah, Esther. Grand Rapids, MI: Baker Academic, 2008. Holladay, William L. A Concise Hebrew, and Aramaic Lexicon of the Old Testament. Leiden, Holland: Brill, 1971), s.v. “שׁוב.” Hubbard, Robert L. The Book of Ruth. New International Commentary on the Old Testament. Grand Rapids, MI: Eerdmans, 1988. Joüon, Paul and Muraoka Takamitzu. A Grammar of Biblical Hebrew. Winona Lake, In: Eisenbrauns, 1978. Kalluveettil, Paul. Declaration and Covenant: A Comprehensive Review of Covenant Formulae From the Old Testament and the Ancient Near East. Rome, Italy: Pontifical Biblical Institute, 1982. Kathleen A. Robertson. “The Book of Ruth.” The New Interpreter’s Bible. Ed. Leander E. Keck. Nashville, TN: Abingdon, 1998. Kautzsch, Emil. Gesenius’ Hebrew Grammar. Trans. Kautzsch Emil, A. E. Cowley, and M. Segal . Oxford, MS: Clarendon, 1990. Keck, Leander E. “Ruth.” The New Interpreter’s Bible 2. Nashville, TN: Abingdon, 1998. Kensky, Tikva Frymer. Reading the Women of the Bible: A New Interpretation of Their Stories. New York, NY: n.p., 2002. Knoppers, Gary N. “Ancient Near Eastern Royal Grants and the Davidic Covenant.” Journal of the American Oriental Society 116 (1996): 670-697. Kutler, L. “A Structural Semantic Approach to Israelite Communal Terminology.” Journal of Near Eastern Studies 14 (1982): 71-72. Lacocque, André. Ruth, A Continental Commentary. Minneapolis, MN: Fortress, 2004. Lapsley, Jacqueline E. “Feeling Our Way: Love for God in Deuteronomy.” Catholic Biblical Quarterly 65 (2003): 350-369 Larkin, Katrina J. A. Ruth and Esther. Old Testament Guide. Sheffield, UK: Academic, 1996. Mathew, Victor H. Judges and Ruth. New Cambridge Bible Commentary. Cambridge, MA: Harvard University Press, 2004. McComiskey, Thomas Edward. The Covenants of Promise: A Theology of the Old Testament Covenants. Grand Rapids: MI: Baker, 1985. Meyers, Jacob M. “Returning Home: Ruth 1:8 and Gendering of the Book of Ruth.” Naomi and Ruth: A Feminist Companion to Ruth. Ed. Athalya Brenner. Shefield, UK: Academic, 1993. Moran, William L. “The Ancient Near Eastern Background of the Love of God in Deuteronomy.” Catholic Biblical Quarterly 25 (1963): 77-87; Nielsen, Kirsten. Ruth: A Commentary. Louisville, KY: John Knox, 1997. Prinsloo, Willem S. “The Theology of the Book of Ruth.” Vetus Testamentum 30 (1980): 332. Rendtorff, Rolf. “The Canonical Hebrew Bible.” Theology of the Old Testament. Ed. David E. Orton. Leiden, Holland: Deo, 2005. Sasson, Jack Murad. Ruth: A New Translation With a Philological Commentary and a Formalist-Folklorist Interpretation. Baltimore, MD: Johns Hopkins University Press, 1979. Smith, Mark S. “Your People Shall be My People: Family and Covenant in Ruth 1:16-17.” CBQ 69 (2007): 246. Soggin, J. Alberto. “שׁוב.” Theological Lexicon of the Old Testament. Ed. Ernest Jenni, Clause Wassermann. Trans. by Mark. E. Biddle. Peabody, MS: Hendrickson, 1997. Thompson, James A., and Elmer A. Martens. “שׁוב.” New International Dictionary of Old Testament Theology and Exegesis. Ed. W. A. VanGemeren. Grand Rapids, MI: Zondervan, 1997. Trible, Phyllis. “A Human Comedy.” God and the Rhetoric of Sexuality: Overtures to Biblical Theology. Ed. Walter Brueggemann, John R. Donahue. Philadelphia, PA: Fortress, 1978. Waard, Jan De, and E. A. Nida. A Translator’s Handbook on the Book of Ruth. London, UK: United Bible Societies, 1973. Waltke, Bruce K., and Charles Yu. Old Testament Theology: An Exegetical, Canonical, and Thematic Approach (Grand Rapids, MI: Zondervan, 2007. Zobel, Hans-Jürgen. “חֶסֶד.” Theological Dictionary of the Old Testament. Ed. G. Johannes Botterweck and Helmer Ringgren. Grand Rapids, MI: Eerdmans, 1977.